Application of Remote Sensing Approaches in Geohazard Risk (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue, entitled "Application of Remote Sensing Approaches in Geohazard Risk”, aims to provide an overview of the application of various advanced remote sensing technologies in geohazard risk identification, monitoring, and mapping. It explores the potential and future prospects of these technologies in terms of enhancing geohazard risk assessment and prediction. This reprint features 10 papers from scholars worldwide, sharing their expertise and insights. We hope that these contributions will help readers to better apply remote sensing methods in geohazard risk assessment.